Harmonization of Personal Data Protection Principles With Electronic Justice Systems In Indonesia - Mardyansyah, Dody Novizar; Sukarmi; Adi Kusumaningrum; Yenny Eta Widyanti (Yuridika, 2025)
Modern digital-based justice is the answer to the challenges of the development of the times. Although modern justice reflects an adaptive judicial body, it must still be equipped with established regulations. This study aims to examine the harmonization of personal data protection principles between the Supreme Court Regulation No. 7/2022 concerning electronic case administration and trials and Law No. 27/2022 concerning Personal Data Protection (PDP Law). In this case, the researcher uses a normative juridical method, with a statutory regulatory and comparative combined approach. This study highlights the norms gap in the Supreme Court Regulation No. 7/2022, particularly in the aspect of protecting the personal data of the parties input into the electronic justice administration system. The main findings exhibited are that the Supreme Court Regulation No. 7/2022 does not regulate the basic principles of data protection as mandated by the PDP Law, which has the potential to cause legal uncertainty and privacy right violations. The fact that the principle of personal data protection in the Supreme Court regulation has not been absorbed is due to the PDP Law, which only came into effect in 2024, even though both were enacted in the same year in 2022. This is seen as weakening the legitimacy of electronic justice in Indonesia. This study is expected to provide a positive contribution in the form of regulatory reform through the revision of the Supreme Court regulations, the establishment of data protection units in the judicial environment, and strengthening institutional coordination. The results of the comparative analysis of common law systems such as England show the importance of integrating data protection principles into the legal infrastructure and institutions of electronic justice to be aware of the protection of privacy rights that intersect with the guarantee of the human rights of justice seekers.